Benchmarking macroprudential policies: An initial assessment - Lombardi, Domenico; Siklos, Pierre L. (Journal of Financial Stability, 2016)
In recognition of the severe consequences of the recent international financial crisis, the topic of macroprudential policy has elicited considerable research effort. The present study constructs, for 46 economies around the globe, an index of the capacity to deploy macroprudential policies. Building on elements that have been the subject of recent research, we develop an index that aims to represent the essence of what constitutes a macroprudential regime. Specifically, the index quantifies: (1) how existing macroprudential frameworks are organized; and (2) how far a particular jurisdiction is from reaching the goals established by the Group of Twenty (G20) and the Financial Stability Board (FSB). The latter is a benchmark that has not been considered in the burgeoning literature that seeks to quantify the role of macroprudential policies.